Umbanda sertaneja: cultura e religiosidade no sertão norte-mineiro - Marques, Ângela Cristina Borges (2007)
The present paper analyses the historic-anthropologic process of umbanda in the North of Minas Gerais State from the mid 1940s to present days. In this sense, it ponders on the dialectical construction of an umbandismo typical from Northern Minas Gerais, formed by the meeting of two types of umbanda in the region: the one from the Southeast and the one from the Northeast. The umbandismo resulting from the shock between the cited trends carries on its rituals and activities elements from the North of Minas Gerais, which denounce the ethos historically constructed in the region, from the cultural meeting between the people from the states of Bahia and São Paulo. We intend to present with this paper that, by following this region's populating process line, the umbanda has suffered and suffers influences, hence translating the hybridization peculiar to the sertanistas and bordering regions. The methodological procedure used in this paper was qualitative, composed by: oral sources with testimony of people who knew and introduced themselves in this religion in the decades of 40, 50 and 60, and of current priests and umbandistas by means of tape recorder and informal conversations; documental survey in public and private heritage; field observation work with the description of rituals; photographs as data source. Thus, from the data crossing obtained in the field, we have come to the following conclusions: the Umbanda Sertaneja translates in its rituals and social relations the axiological issue present in the history of the region, the tension between the good and the evil; the arrival of camdomblé in this region at a posterior time has provoked the introduction of umbandistas priests in this religion without, however, characterizing the abandonment of umbanda; in some temples, this introduction provokes the formation of a religious continuum formed by the triad umbanda, quimbanda and candomblé which signals the emergence of a new religious logic; the figure of Exu presents itself in this new logic as the main personality insofar as it establishes, in the mentioned triad, the role of axis and connection besides revealing aspects of the norte mineiro ethos